University Decission Support System for Promotion Strategy Using Topsis Method - Pradityo Utomo; Arief Budiman (Universitas Bina Darma, 2021)
Campus or college is a place of education for people to seek knowledge. One of the essential components of campus sustainability is the existence of students. For this reason, each campus must have the right strategy in carrying out promotions, especially during the Covid-19 Pandemic as it is today. Because in a pandemic like this, many people are inevitably aware of the economy and health. So, the campus must have a strategy where the community continues to respond to the campus's promotions. Among the several promotional strategies to be right on target in this pandemic are conducting webinars, television broadcasts, radio broadcasts, advertisements on social media, placing banners, distributing pamphlets, and distributing campus marches. In carrying out promotions, wherever possible, keep prioritizing health by reducing the risk of covid-19 transmission. The promotion strategy in this pandemic must also pay attention to several factors for its implementation including available costs, human resources involved, the location of the activity implementation, the number of activities, and the risks associated with covid-19. From several promotional strategies and factors that support the smooth running of activities, a decision support system can be made that can help determine the campus promotion strategy. Decision Support Systems made using the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method approach.Furthermore, the developing of decision support systems using the waterfall system development method. Based on the results and discussion of this study, it concluded that the TOPSIS method could be used to determine campus promotion strategies during the Covid-19 pandemic by building a decision support system. The results of determining the promotion strategy with a decision support system obtained the greatest value lies in V4, which means that the strategy for using social media is the most suitable for campus promotion during the Covid-19 pandemic.